Effects of cluster size and substrate temperature on the homoepitaxial deposition of Au clusters - Lee, SC; Yu, BD; Kim, DY; Hwang, NM (ELSEVIER SCIENCE BV, 2002)
Effects of cluster size and substrate temperature on the dynamics behavior of deposited An clusters were simulated by molecular dynamics using a semi-empirical embedded-atom method. In this simulation, three different cluster sizes of 321, 1055, and 1985 atoms clusters were deposited homo-epitaxially on a An (0 0 1) substrate at substrate temperatures of 300, 700, and 1000 K. The small cluster size and the high substrate temperature favored the epitaxial recrystallization of the clusters. In the case of the 321-atom cluster, the epitaxial recrystallization was observed at all substrate temperatures. When 1055- and 1985-atom clusters were deposited, planar defects such as twins or grain boundaries were observed at a low temperature of 300 K. At elevated temperatures, the planar defects were gradually diminished. At 1000 K, epitaxial recrystallization was observed regardless of the cluster size. These results agree with the suggestions made in the charged cluster model (J. Crystal Growth 162 (1996) 55). (C) 2002 Published by Elsevier Science B.V.
Keywords: EMBEDDED-ATOM METHOD; MOLECULAR-DYNAMICS; CVD PROCESS; MODEL; METALS; DIAMOND; EVAPORATION; SURFACES; BEHAVIOR; GOLD